2014
DOI: 10.2217/nmt.14.33
|View full text |Cite
|
Sign up to set email alerts
|

The sleep–wake Cycle and Alzheimer’s Disease: What do We know?

Abstract: SUMMARY Sleep–wake disturbances are a highly prevalent and often disabling feature of Alzheimer’s disease (AD). A cardinal feature of AD includes the formation of amyloid plaques, associated with the extracellular accumulation of the amyloid-β (Aβ) peptide. Evidence from animal and human studies suggests that Aβ pathology may disrupt the sleep–wake cycle, in that as Aβ accumulates, more sleep–wake fragmentation develops. Furthermore, recent research in animal and human studies suggests that the sleep–wake cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 105 publications
5
95
2
4
Order By: Relevance
“…Depression as the most pronounced clinical symptom is considered as a risk factor for neurodegeneration (Donovan et al, 2015). AD patients also typically show sleep fragmentation with frequent awakenings during the night, and a propensity to sleep during the daytime (Ancoli-Israel et al, 1994; Lim et al, 2014). Recent animal studies confirmed how early occurence of AD pathology in serotonergic nuclei leads to wake-sleep cycle disturbances (Sterniczuk et al, 2010; Roh et al, 2012).…”
Section: Chemical Neuroanatomy Of the Monoaminergic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression as the most pronounced clinical symptom is considered as a risk factor for neurodegeneration (Donovan et al, 2015). AD patients also typically show sleep fragmentation with frequent awakenings during the night, and a propensity to sleep during the daytime (Ancoli-Israel et al, 1994; Lim et al, 2014). Recent animal studies confirmed how early occurence of AD pathology in serotonergic nuclei leads to wake-sleep cycle disturbances (Sterniczuk et al, 2010; Roh et al, 2012).…”
Section: Chemical Neuroanatomy Of the Monoaminergic Systemsmentioning
confidence: 99%
“…In fact, recent data showed that plaque formation in the brain of the APPswe/PS1ΔE9 mouse model of AD causes the deterioration of the sleep-wake cycle and loss of diurnal fluctuation of Aβ measured in the interstitial fluid (Roh et al, 2012). In addition to the effect that accumulated Aβ causes sleep deprivation, it has been shown that sleep deprivation leads to the inadequate clearance of Aβ (Roh et al, 2012; Ju et al, 2013; Lim et al, 2014; Šimić et al, 2014), contributing to more Aβ accumulation and creating a vicious circle. Besides Aβ release from raphe projection axons (Braak and Del Tredici, 2013), accumulation of Aβ due to sleep deprivation may also add to the pathology of raphe and other brainstem nuclei, particularly in the ‘pre-tangle’ stage.…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…3b). Disruptions can also be caused by social or environmental factors, such as shift work or jet lag, or by disease states that involve circadian disruption including Parkinson's and Alzheimer's disease (Karatsoreos 2014;Lim et al 2014;Ondo 2014;Sterniczuk et al 2014). As such, circadian problems are often a marker of a number of diseases.…”
Section: Amplitude Of Scn Oscillationmentioning
confidence: 99%
“…The primary risk factors for AD include advancing age [27][28][29], nutritional patterns characterized by low intake of plant-derived foods [30], together with metabolic syndrome-related dysfunctions (e.g., cardiovascular disease and diabetes) [8,31], low socioeconomic status and a low level of educational attainment [32][33][34], low level of daily physical activity [35,36], and low cognitive training [37]. Additionally, sleep disorders [38][39][40], known to positively correlate to early A␤ deposition [41,42], exposure to air pollution [43], smoking [44], and the intake of metals (e.g. aluminum [45], dietary copper [46], and manganese [47]) have been described as possible risk factors.…”
Section: The Population and Individual Levels: Epidemiological Studiementioning
confidence: 99%